TACTICS - A HISTORICAL SURVEY - Johnson, A.G. (Scientia Militaria - South African Journal of Military Studies, 2012)
The study of military tactics down the ages reveals a surprising lack of innovations and an even more surprising reluctance to follow up those that have been made.